Health informatics improving patient care (British Informatics Society Ltd., 2012)
Health informatics and technology are great enablers of health care. They can help raise productivity, empower patients, improve efficiency and reduce risk. This ebook contains a stimulating selection of material by HI experts on the latest developments. Readers do not require a detailed understanding of health care or health informatics.
Includes bibliographical references
Keywords: Medical informatics; Médecine; Informatique; MEDICAL; Allied Health Services; Medical Technology; MEDICAL; Biotechnology; MEDICAL; Family & General Practice; MEDICAL; Lasers in Medicine; TECHNOLOGY & ENGINEERING; Biomedical